The Students’ Writing Ability and Their Learning Attitude Taught by Draw Label and Caption Technique in Indonesia - Setiyawati, Eka Pra (Jurnal Pendidikan Progresif, 2017)
The student’s writing ability and their learning attitude taught by draw label and caption technique in Indonesia.This research investigated about the implementation of Draw Label and Caption (DLC) to improve the students’ ability in writing descriptive text. The researcher used the following data analysis technique; coding the students, rating their works with two raters, and t test, descriptive statistics of learning attitude and calibration. The result showed that the students’ average score in pre-liminary was 58.21, in cycle-1 was 63.38, and in cycle-2 was 74.68. The students’ attitude was improved marked with the increasing number of students who liked the DLC model of teaching.Upon this research it can be concluded that the students’ ability in writing descriptive text is improved and reached the target of score.  Keywords: DLC, descriptive text, CARDOI: http://dx.doi.org/10.23960/jpp.v7.i1.201701